1999
DOI: 10.1097/00003246-199906000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Impaired inducibility of heat shock protein 70 in peripheral blood lymphocytes of patients with severe sepsis

Abstract: Inducibility of ex vivo heat shock protein 70 was impaired in peripheral blood lymphocytes of patients with severe sepsis. The impaired expression of the potentially protective heat shock protein 70 may contribute in vivo to immune dysfunction, because intact functioning of T and B lymphocyte responses is of central importance in resisting infection in severe sepsis. Monitoring of inducible heat shock protein 70 in peripheral blood lymphocytes may contribute to the evaluation of the immune consequences of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 29 publications
2
19
0
2
Order By: Relevance
“…At the same time, exogenous HSP70 can be used for the prophylactic treatment of various types of sepsis (Vinokurov et al 2012). The mechanisms (Aschkenasy et al 2011;Schroeder et al 1999) involved suggest that HSP70 can impair apoptotic cellular pathways via interactions with caspases; HSP70 causes impairment of peripheral blood lymphocytes (including T and B lymphocytes), consequently resulting in immune dysfunction and severe secondary sepsis.…”
Section: Changes In the Significance Of Hsp70 Levels In Inflammation mentioning
confidence: 99%
“…At the same time, exogenous HSP70 can be used for the prophylactic treatment of various types of sepsis (Vinokurov et al 2012). The mechanisms (Aschkenasy et al 2011;Schroeder et al 1999) involved suggest that HSP70 can impair apoptotic cellular pathways via interactions with caspases; HSP70 causes impairment of peripheral blood lymphocytes (including T and B lymphocytes), consequently resulting in immune dysfunction and severe secondary sepsis.…”
Section: Changes In the Significance Of Hsp70 Levels In Inflammation mentioning
confidence: 99%
“…Preemptive Hsp70 induction protects cells against cytotoxic mediators and reduces organ dysfunction and mortality in animal models of sepsis [14]. Under conditions with low plasma glutamine, such as polytrauma, severe sepsis and acute respiratory distress syndrome, the expression of Hsp70 was found to be impaired in granulocytes [15], monocytes [16] and lymphocytes [17]. It was shown in vitro in isolated lymphocytes that Hsp70 induction depends on the availability of glutamine in a dosedependent manner [18].…”
Section: Cell Stress Response In Glutamine-starving Cellsmentioning
confidence: 99%
“…It is likely that this GLN deficiency leads to a condition in which the patient is unable to induce HSP expression appropriately. Preliminary studies in immune cells taken from critically ill patients support this conclusion [14,15]. This would place the critically ill individual in a compromised position in which appropriate tissue protection, immune regulation, and preservation of metabolic function could be significantly impaired.…”
Section: Resultsmentioning
confidence: 95%
“…Our laboratory has explored all of these mechanisms as possible contributing mechanisms to GLN's benefit in critical illness and injury. We have observed that a central theme in GLN's beneficial effects may involve enhanced expression of HSP, specifically HSP-70 [13,15]. Enhanced HSP expression may play a role in all of the aforementioned proposed mechanisms of GLN's benefit in clinical illness.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation